Economic integration and industrial agglomeration - Venables, Anthony J. (Economic & Social Studies, 1994)
This paper reviews recent research on industrial location, focusing on the way in which reducing barriers to trade may induce relocation of industry. Integration may cause industries to agglomerate in a few locations, this causing divergence of the structure of integrating economies, and possibly also divergence of income levels. Smaller locations will have lower real wages than large ones, although in the limit ? as trade costs go to zero ? factor price equalisation occurs.
Keywords: Economic integration; Industrial agglomoration; Industrial location